Physical and Mechanical Properties of Concrete with Locally Produced Metakaolin and Micro-silica as Supplementary Cementitious Material - Khan, S.U. (Springer Science and Business Media Deutschland GmbH, 2020)
Malaysia is among the countries that have abundant reserves of raw material to be used to form metakaolin (MK). Only a few studies are available in the literature, which examines the potential of the development of metakaolin through calcination and its use as supplementary cementitious material (SCM). The use of MK as SCM is essential to utilise the local resources and to reduce the carbon footprint and embodied energy in the use of cement. Thus, MK developed at laboratory scale, produced through using local source, is compared with the commercially available micro-silica by investigating their properties in this paper. The concrete made of MK and micro-silica was tested under compression, split tension and bending. The comparison of the phase difference between MK and micro-silica had carried out through X-ray diffraction pattern. Besides, an interfacial transition zone of concrete made of MK and micro-silica had observed through field emission scanning electron microscopy. A total of three mixes of concrete had prepared, out of which one was without cement replacement and served as control mix. The remaining two mixes were 10 cement replacement with micro-silica and MK. The results showed that MK has high reactivity with portlandite in concrete due to its irregular structure and the amorphous phase. The compressive strength was 4 higher with MK as compared to micro-silica at an early age. MK concrete displayed a higher split tensile strength of approximately 14 and 35 and a higher load-carrying capacity of approximately 15 compared to micro-silica and competitive with control concrete at ages 7â90Â days. Â© 2020, Shiraz University.